Korelasi Hafalan Al Qur’an Dengan Prestasi Belajar Pendidikan Agama Islam - Ulum, Misbahul (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2022)
Memorizing the Qur'an is an attempt to stick in the memory and heart of the verses that have been memorized. So that in an effort to memorize requires high concentration so that memorization can survive well. The habit of a memorizer in concentrating, so that when a person memorizes more often it will affect his ability to learn. High learning ability will make high learning achievement as well. To achieve this research goal, quantitative approaches with this type of correlational research are used.Data is collected using documentation then analyzed using simple linear regression analysis. Next to find out how much the relationship of qur'anic memorization activities to the achievement of learning Islamic Education using the calculation of R square from SPSS output. The results showed that: (1) The learning achievement of students of class IX in islamic religious education subjects meets graduation standards with a value of 70-80 amounting to 2 children, the value of 81-90 amounted to 13 children, the value of 91-100 amounted to 17 children. (2) The influence between the level of memorization ability of the Qur'an and the learning achievement of students whose percentage results amounted to 18.4% while 81.6% was determined by other factors.